Neuroticism is the best predictor of lower emotional resilience during the COVID‒19‐related confinement periods. (31st December 2021) - Gonneaud, Julie; Paly, Léo; Delarue, Marion; Mézenge, Florence; Fauvel, Séverine; Lefranc, Valérie; Cognet, Aurélia; de Flores, Robin; Touron, Edelweiss; Marchant, Natalie L; Poisnel, Géraldine; Chetelat, Gaël; et al.
Abstract: Background: The COVID‐19 pandemic and the associated distancing measures dramatically affect psychoaffective health, and this is accentuated in older adults who are more vulnerable to the situation. In this study, we are interested in the predictors of emotional resilience in healthy older adults, and also on how the repetition of confinement periods could influence this resilience and its predictors. Method: 102 cognitively unimpaired older adults from the Age‐Well cohort were included. They all completed the Depression Anxiety Stress Scales (DASS‐42) during each period of national confinement (April and November 2020), used here as a measure of emotional resilience (lower scores indicating greater resilience). Baseline measures from the Age‐Well study, all acquired before the pandemic, were used as predictors, including demographics (age, sex, education), personality (Big Five Inventory), psychological (anxiety [STAI‐B], depression [GDS]), lifestyle (Lifetime of experience questionnaire), global cognitive functioning (Mattis‐DRS) and neuroimaging data (hippocampal volume, brain perfusion, amyloid burden). We ran stepwise regressions to predict emotional resilience during the first confinement. Then, we used paired t‐test to assess the evolution of emotional resilience between the two confinements. Finally, we replicated the stepwise regressions to predict changes in resilience over time ('second‐minus‐first' confinement). Result: Neuroticism was the only significant predictor of the DASS‐42 score during the first confinement (β=.48; p<.001; Figure‐1), lower neuroticism being associated with better resilience. We found the DASS‐42 score to increase significantly from the first to the second confinement, indicating decreased emotional resilience over time. Moreover, higher neuroticism (β=.53; p<.001) and higher agreeableness (β=.20; p=.03) were associated with higher DASS‐42 increase over time (Figure‐2). Conclusion: Our study suggests that lower neuroticism is the main predictor of greater emotional resilience to the COVID‐19‐related confinement. Importantly, the repetition of the confinement situation is associated with a decrease in emotional resilience in older adults, especially if they are prone to experience distress (neuroticism) or have a particularly social personality (agreeableness). Overall, these results underline the increasing need, as the crisis persists, for a psychoaffective support of older adult.